Encouraging Learners' Writing Engagement: The Role of a Life Project Based on Students Interests (2022)
ABSTRACT: This action research paper relates the experience of a teacher-researcher with an eighth-grade group in the public school Institución Educativa Lucrecio Jaramillo in Medellín. The purpose of this study was to encourage learners’ writing engagement using a life project based on their interests. Actions included the implementation of a life project and design of activities according to the students’ interests oriented by a teaching and learning cycle, scaffolding strategies and the genre-based approach. The data collection instruments were a questionnaire, teacher journals, students’ artifacts, and focus group interviews. Findings showed that the design of activities according to the students' interests mediated through a teaching and learning cycle and scaffolding strategies could improve writing engagement as well as writing production.